PENGARUH MODEL PEMBELAJARAN INQUIRY BERBASIS MEDIA VISUAL TERHADAP HASIL BELAJAR MATERI SISTEM KEKEBAL TUBUH KELAS XISMA NEGERI 1 PALIPI T.A 2021/2022 - CHRISTINE A SINAGA; MASNI VERONIKA SITUMORANG; WINARTO SILABAN (JURNAL ILMIAH KOHESI, 2022)
This study aims to determine the effect of visual media-based inquiry learning model on student learning outcomes on immune system material. This type of research is a quasi-experimental research design using the Nonequivalent Control Group Design. This research sample uses the entire population class because it only has 2 classes. The data collection method is a multiple choice test, equipped with documentation. The results of data analysis show that the learning outcomes of the control class are included in the low criteria and the learning outcomes of the experimental class are in the medium criteria.